Development of Internet of Things-Based Room Security using Telegram - Tullah, Rahmat; Sofia, Detin; Hafidin, Alfa (JURNAL SISFOTEK GLOBAL, 2024)
Security plays a very important role in various aspects, one of which is the security of a home room which is a building for a residence. Currently, there are still many home security system devices circulating on the market that are considered ineffective in their use and cost. In addition, the home security system cannot provide warning notifications when home security is threatened and send the latest conditions of the house. This study designs a home room security system using the Internet of Things (IoT) based on Telegram Messenger. When the Passive Infrared Receiver (PIR) sensor detects movement, the OV2460 camera on the ESP32-Cam module will take a picture and then send it to the homeowner as a form of home security warning via a bot on Telegram Messenger. When the Flame Sensor detects a fire, the Buzzer will sound and then send a notification in the form of a fire warning. The results of this study showed that the home room security that was created was able to detect movement at an effective distance of the PIR sensor of 1 - 6 m and the presence of fire on the Flame Sensor which has a wavelength between 760nm - 1100nm. For the next researcher, they can develop a camera that can detect faces (face detection) and face recognition.